EDUCATION ON HYPERTENSION PREVENTION FOR GENERATION Z - Tahara Dilla Santi; Aditya Candra; Ika Waraztuty; Andri; Muhammad Yani; Said Aandy Saida (RADJA PUBLIKA, 2025)
Hypertension is a significant public health problem and a risk factor for cardiovascular disease and other complications. According to Riskesdas data, the prevalence of hypertension sufferers under the age of 18 was 25.8% in 2013 and increased to 34.1% in 2018. This community service aims to increase the knowledge of Generation Z, namely students who live in the Muhammadiyah Patronage House in Banda Aceh City. Educational activities were carried out using the Participatory Action Research (PAR) method and were carried out on October 27, 2024, at the Muhammadiyah Patronage House prayer room with 25 students as participants. Participants were given a knowledge questionnaire before and after the activity, and the data were analyzed using SPSS. The extension instrument was a PowerPoint presentation. Educational activities took place in an orderly and smooth manner and had a positive impact on increasing student knowledge.